Terebovlia as the Location for the Polish Troops’ Stay in 1557 and 1558 (City and War, 2022)
In 1557 and 1558, Terebovlia was the place of the stay of the Polish army, whose task was to defend the Ruthenian lands of the Kingdom of Poland against the Tatar invasions. Surviving written records contain information about the Polish mercenary army staying in the town – the number, composition, armament, and commanders of the troops. According to these sources, in 1557 more than 1000 mounted soldiers passed through the town, and a similar number of troops visited the town in the following year. At that time, Terebovlia was not the only meeting place for the army that was supposed to stop the Tatar raids, but it was here that the largest number of them was gathered. In 1558, the mercenaries participated in a battle against the Crimean Tatars, who were then invading the south-eastern lands of the Kingdom of Poland. There were some military actions against the invaders, but they were not big battles – rather small skirmishes that took place in the area from Terebovlia to Bar, between the rivers Dniester and Boh. For these troops, Terebovlia was a relatively safe place in the immediate vicinity of the ongoing war.